ANALYSIS OF RECOGNITION OF INCOME AND EXPENSES OF BUMDESMA - Dwi Rofi'Ati; Lis Setyowati; Abdul Manan (International Journal of Economics, Science, and Education, 2024)
Analysis of Income and Expense Recognition of Bumdesma Podo Rukun during the 2021 Covid-19 Period in Wilangan District, Nganjuk City.The aim of this research is to analyze the Recognition of Income and Expenses of Bumdesma Podo Rukun during the 2021 Covid-19 Period in Wilangan District, Nganjuk City. This research was carried out from November to July 2022, where primary data was obtainedfrom the object under study or the main source by observing cases that have been encountered directly. This data was collected using qualitative methods or through field surveys, interviews and documentation. To collect this data the author carried out data presentation, data reduction and conclusions.Based on the results of research and discussion, it shows that in 2021 Bumdesma Podo Rukun, Wilangan District, Nganjuk City, the recognition of income and expenses uses the accrual basis method and is in accordance with PSAK 23.